Recombinant expression of mutations causing von Willebrand disease type Normandy: characterization of a combined defect of factor VIII binding and multimerization - Schneppenheim, Reinhard; Lenk, Harald; Obser, Tobias; Oldenburg, Johannes; Oyen, Florian; Schneppenheim, Sonja; Schwaab, Rainer; Will, Kerstin; Budde, Ulrich (Thrombosis and Haemostasis, 2004)
Von Willebrand disease type Normandy (VWD 2N) is caused by mutations at the factor VIII (FVIII) binding site of VWF, located at the amino-terminus of mature VWF. It is inherited in a recessive fashion and both homozygous and compound heterozygous mutations have been identified. Homozygous mutations are correlated with a clinical phenotype indistinguishable from mild hemophilia A by conventional laboratory tests, whereas compound heterozygosity with a quantitative defect may appear as VWD type 1 (VWD1). We have now identified and expressed a novel heterozygous mutation (Y795C) which is responsible for both, a defective FVIII-binding and aberrant multimers in a female patient with mild FVIII deficiency. Additionally we expressed another mutation (E787K), previously identified by us in a male patient with a severe ‘pseudohemophilic’ phenotype. Analysis of the FVIII binding and the multimer structure of the respective recombinant VWF mutants reproduced the observed phenotype: the FVIII binding defect in addition to the aberrant multimer structure of the patient with Y795C and the FVIII binding defect only, in the patient with E787K. Our results demonstrate the causative nature of the two mutations and emphasize the impact of ‘cysteine mutations’ on the multimer structure of VWF.
Keywords: von Willebrand factor; von Willebrand disease type 2N; multimer structure